Multi-type interior permanent magnet motor driving system - Mazalan, Siti Khodijah (2011)
The newly built and specially designed three phase Multi-type Interior Permanent Magnet (MTIPM) motor has led to an invention of the new driving system. The new motor has a special phase independent coil winding and multiple configurations,Permanent Magnet Brushless Direct Current (BLDC) motor and Permanent Magnet Stepper (PMST) motor, which has a specialty in high speed and high torque at low speed function. Therefore, it is potentially suitable for multi-functional and in-wheel motor applications. Latest trend of conventional motor usually has a single configuration and simplistic driving order that makes none of the existing driving system is suitable for the MTIPM motor. This motor needs a system which can drive multiple configurations and handle the complexity of switching decision and speed control in real time. Thus, a specially designed driving system is essential to drive and control this special motor. The MTIPM motor driving system is proposed as a new driving and control method for the MTIPM motor. This driving system is capable of driving multiple configurations with a combination of BLDC and PMST motor drivers and a main driving controller. The aims are to achieve smooth switching drive in between the configurations while the motor is running and to provide speed control technique for both configurations. In this research, combinations of conventional BLDC and PMST motor driver topologies are used to design the MTIPM motor driving system. In addition, National Instrument, (NI) USB-6229 Data Acquisition (DAQ) card is used to act as the main driving controller for the driving system, where it is programmed, monitored and controlled using the NI LabVIEW software in the visual programming language. This programming NI DAQ card controls the selection of drivers, switching interface, motor speed, stops and starts up of the motor by sending a signal to the driving circuit. Constantly, the NI DAQ card requires a continuous feedback signal from the motor to decide on any changes of the motor driving behavior. Prior to the development of this new driving system, the system is evaluated in several laboratory experiments. The conducted studies in this research show the MTIPM motor behavior while driven by the driving system which is presented in the supply voltage, motor current, motor speed and Hall-effect voltage characteristic,switching state characteristic, speed characteristic, torque versus speed characteristic and load effect characteristic. The results demonstrate the motor real performance and it is elaborated in this thesis. Generally, by the evaluation studies, it is proven in this research that the new invented driving system serves its purpose in demonstrating a switching drive and control for the special built MTIPM motor. BLDC motor has the advantage in high speed application while the PMST motor has reputation in low speed and positioning application. Hence, with this new driving system, the driven MTIPM motor can combine the advantage of BLDC and PMST motor in one system. To end with, it can be concluded that the objectives stated earlier are successfully achieved with the built of MTIPM motor driving system in this research.